Estrat??gia para implementa????o de trabalho colaborativo : um estudo de caso na EMAE - Empresa Metropolitana de ??guas e Energia S.A. - Ara??jo, Jos?? Braz de (2003)
The chase for proceeds by companies, allied to the fast technological evolution observed during the last decades, has promoted organizational and mannering changes in the corporative environment, where the information assumes a primordial feature in the enterprise activities. Easiness, agility, quickness and security in the information flow are critical factors to get competitiveness, through costs reduction and excellency of services. In this context, the implementation of collaborative work, supported by computer tools, becomes essential due to the volume of processed information and the complexity of the distribution and the control of these information. The goal of this work is to present the ???computer supported collaborative work??? as fundamental element for the corporative information flow, presenting a strategy aiming at its implementation in a big company of mixing economy of the State of S??o Paulo, taking as case study. This strategy is seated in the objectives to reduce the transit of documents and bureaucracy and to allow the fast access to the information, assisting the decisions making.